Experimental data on the production and characterization of biochars derived from coconut-shell wastes obtained from the Colombian Pacific Coast at low temperature pyrolysis (2020)
Biochars are emerging eco-friendly products showing outstanding properties in areas such as carbon sequestration, soil amendment, bioremediation, biocomposites, and bioenergy. These interesting materials can be synthesized from a wide variety of waste-derived sources, including lignocellulosic biomass wastes, manure and sewage sludge. In this work, abundant data on biochars produced from coconut-shell wastes obtained from the Colombian Pacific Coast are presented. Biochar synthesis was performed varying the temperature (in the range: 280 °C–420 °C) and O2 feeding (in the range: 0–5% v/v) in the pyrolysis reaction. Production yields and some biochar properties such as particle size, Zeta Potential, elemental content (C, N, Al, B, Ca, Cu, Fe, K, Li, Mg, Mn, Na, P, S, Ti, Zn), BET surface area, FT-IR spectrum, XRD spectrum, and SEM morphology are presented. This data set is a comprehensive resource to gain a further understanding of biochars, and is a valuable tool for addressing the strategic exploitation of the multiple benefits they have. © 2019 The Author(s)